Analisa Pengaruh Penggunaan Aplikasi E-Soil Terhadap Kemudahan dalam Melihat Informasi Kesuburan Tanah - Estu Handayani; Ahmad Chusyairi (Teknomatika, 2019)
In this technological advancement, information is needed on soil fertility for agricultural entrepreneurs. This information is carried out using the E-Soil application in identifying soil color and web information for spatial rice fields and soil fertility. The usefulness of this application is to regulate the utilization of agricultural land appropriately and optimally. To find out how much influence the use of E-Soil application is made, an analysis is carried out by collecting data using questionnaires and the data is processed using validity and reliability tests. The next step is checking using classical assumptions, and analysis using simple linear regression and multiple linear regression. The study was conducted in Singojuruh Subdistrict towards farming businesses. The results of this research are farm business and information technology variables that have a moderate and strong relationship to the ease of use of E-Soil applications. This variable also has a significant effect on the ease of use of the E-Soil application.